PEMBERDAYAAN PENYULUH AGAMA DALAM PENINGKATAN PELAYANAN KEAGAMAAN DI KOTA MEDAN (Harmoni, 2014)
The aims of this study are to evaluate the The aims of this study are to evaluate the effectiveness of the implementation of the 1999 State Ministerial Decree No. 54 / KEP / MK.WASPAN / 9/1999 by the National Coordinator for the Development, Monitoring and Empowerment of the State Apparatus. This decree focused on the functional role of religious counselors and their accreditation. This paper seeks to explore the factors that facilitate and obstruct the fulfillment of religious counselorsΓÇÖ duties. This study uses qualitative methods such as interviews, focus group discussions and archival work. Data was collected in April and May of 2013 in Medan. This study shows that most religious counselors understand the contents of the State Ministerial Decree, but they have not consistently implemented it. Support from the Ministry of Religious Affairs for religious counselors is still inadequate. Religious counselors have very limited resources and they are not wellequipped to deal with a more dynamic society. Religious counselors find it difficult  to achieve the number of credits required by the state, especially the levels of IV/a and IV/b due to these limited resources. The number of Islamic religious counselors and Buddhist religious counselors is still quite low and there is still a great deal of demand for counselors. The outcome of the decree is still unknown. Until then, the facilities and infrastructure prepared by the government is too limited, thus inhibiting the performance of counselors in the field.
Keywords: Religious Counselors; Service; Empowerment; Penyuluh Agama; Pelayanan; Pemberdayaan